2018
DOI: 10.26444/jpccr/99878
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroergotamine (DHE) – Is there a place for its use?

Abstract: Nowadays, dihydroergotamine (DHE) is sporadically used as a vasoconstrictor in the treatment of acute migraine. The importance of this drug in medicine has significantly decreased in the recent years. Limitations on the use of dihydroergotamine are due to the high toxicity and increased the risk of severe adverse events after prolonged theraphy. The Committee for Medicinal Products for Human Use of the European Medicines Agency recommends limiting the use of drugs that contain ergotamine derivatives due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…While no good data regarding ergotamine s elimination half-life and its other pharmacokinetic parameters appear to be generally available, clinical experience of the apparent duration of action of a single oral dose of the drug suggests that, whether in the form of the parent substance or its metabolites, it could be effective for around 12 h or longer after intake. The elimination half-life of dihydroergotamine is around 12 h [47].…”
Section: Strategically Timed Preventionmentioning
confidence: 99%
“…While no good data regarding ergotamine s elimination half-life and its other pharmacokinetic parameters appear to be generally available, clinical experience of the apparent duration of action of a single oral dose of the drug suggests that, whether in the form of the parent substance or its metabolites, it could be effective for around 12 h or longer after intake. The elimination half-life of dihydroergotamine is around 12 h [47].…”
Section: Strategically Timed Preventionmentioning
confidence: 99%
“…Administration of dihydroergotamine via inhalation was demonstrated to be superior to a placebo in relieving migraine symptoms, with or without aura in adults, and sustaining relief in patients who experience nausea or vomiting, photophobia and phonophobia. Pharmacokinetic studies demonstrated that inhaled dihydroerhotamine demonstrated rapid absorption (t max of 10 min), high bioavailability (77%) and long t 1/2 (15 h), thus succeeding low oral bioavailability and absorption, in addition to avoiding patient suffering from being repeatedly injected intravenously [6].…”
Section: Inhaled Delivery Of Anti-migrainesmentioning
confidence: 99%
“…Current indications for DHE cover mainly acute migraine management. Although some new drugs, such as triptanes, were introduced to therapy, dihydroergotamine still occurs in recommendations [8][9][10]. There are also data supporting the use of DHE in menstrual migraine, migraine with central sensitization and cutaneous allodynia, medication-overuse headache, migraine recurrence, and migrainous state [11].…”
Section: Introductionmentioning
confidence: 99%